A microdevice for rapid, monoplex and colorimetric detection of foodborne pathogens using a centrifugal microfluidic platform - Sayad, A.; Ibrahim, Fatimah; Uddin, S.M.; Cho, J.; Madou, M.; Thong, Kwai Lin (Elsevier, 2017)
Outbreaks of foodborne diseases have become a global health concern; hence, many improvements and developments have been made to reduce the risk of food contamination. We developed a centrifugal microfluidic automatic wireless endpoint detection system integrated with loop mediated isothermal amplification (LAMP) for monoplex pathogen detection. Six identical sets were designed on the microfluidic compact disc (CD) to perform 30 genetic analyses of three different species of foodborne pathogens. The consecutive loading, mixing, and aliquoting of the LAMP primers/reagents and DNA sample solutions were accomplished using an optimized square-wave microchannel, metering chambers and revulsion per minute (RPM) control. We tested 24 strains of pathogenic bacteria (Escherichia coli, Salmonella spp and Vibrio cholerae), with 8 strains of each bacterium, and performed DNA amplification on the microfluidic CD for 60 min. Then, the amplicons of the LAMP reaction were detected using the calcein colorimetric method and further analysed via the developed electronic system interfaced with Bluetooth wireless technology to transmit the results to a smartphone. The system showed a limit of detection (LOD) of 3 × 10−5 ng μL−1 DNA by analysing the colour change when tested with chicken meat spiked with the three pathogenic bacteria. Since the entire process was performed in a fully automated way and was easy to use, our microdevice is suitable for point-of-care (POC) testing with high simplicity, providing affordability and accessibility even to poor, resource-limited settings.